The Extracellular Matrix in Epithelial Ovarian Cancer – A Piece of a Puzzle - Cho, Angela; Howell, Viive M.; Colvin, Emily K. (Frontiers in Oncology, 2015)
Epithelial ovarian cancer is the fifth leading cause of cancer related deaths in women and the most lethal gynecological malignancy. Extracellular matrix (ECM) is an integral component of both the normal and tumor microenvironment. ECM composition varies between tissues and is crucial for maintaining normal function and homeostasis. Dysregulation and aberrant deposition or loss of ECM components is implicated in ovarian cancer progression. The mechanisms by which tumor cells induce ECM remodelling to promote a malignant phenotype are yet to be elucidated. A thorough understanding of the role of the ECM in ovarian cancer is needed for the development of effective biomarkers and new therapies.